Association Between Body Mass Index, Physical Activity, Stress Level, and Hypertension in Kalirejo Residents - Harlinda, Nadya Meta; Praba, Venansya Maulina; Raniasari, Nisrina Nabila; Heriqbaldi, Ayurveda Zaynabila; Tessari, Chelssi Gloria; Putri, Natasya Ariesta Selyardi; Fachryandini, Nofita; Paramarta, Made Bayu Angga; Sudaryani, Sudaryani; Utomo, Budi; Fauziyah, Shifa (Jurnal Promosi Kesehatan Indonesia, 2024)
Background: Hypertension is amongst the top 10 non-communicable diseases and is the leading cause of premature death worldwide. Multiple factors contribute to the occurrence of hypertension. Risk factors include modifiable ones, such as lifestyle, smoking habits, sleeping patterns, caffeine consumption, physical activity, high-sodium diet, and stress levels. On the other hand, factors such as gender and age are non-modifiable. A primary survey in Kalirejo, Lawang, showed that hypertension is the leading health issue. This research aims to analyze the association between body mass index, physical activity level, and stress level with hypertension in Kalirejo, Lawang.Method: This research is a correlative analytical descriptive study using the cross-sectional method that involves 99 residents aged ≥ 45 years old in Kalirejo. Results: This study revealed that the largest age group in Kalirejo is elderly people, with most respondents being female, non-smokers, and with no family history of hypertension. A majority of the respondents consume caffeine and use minimal salt. The largest BMI distribution is within the normal category (41.4%). High physical activity is found to be more frequent (45.5%), and stress level is primarily low (62.6%). Bivariate analysis shows a significant association between BMI and hypertension (p<0.05). Meanwhile, physical activity and stress levels are irrelevant to the occurrence of hypertension. This study discovered that there is a significant association between BMI and hypertension, and a non-significant association between physical activity and stress level with hypertension, respectively, among pre-elderly and elderly residents in Kalirejo.